Recording the Warm-Up Methods Which the Greek Coaches Uses in 11 – 12 Years Old Swimmers at 100m Freestyle - Topalnakou, Γεωργία; Papadimitriou, Κωνσταντίνος; Papadimitriou, Νίκος; Loupos, Δημήτριος (Inquiries in Physical Education and Sport, 2022)
Warm - up is an integral part before the participation in any activity. An interesting scientific field is about the effect of warm-up at the swimming performance on childhood swimmers. The purpose of this study was to record what the Greek swimming coaches choose as a warm – up method in childhood swimmers before the races of 100m freestyle. In the study participated 70 Greek coaches aged 35 ± 11 years. They replied to a questionnaire which contains 34 questions about the content of a warm - up before 100m freestyle in 11 – 12 years old swimmers. For the data analyzation was used descriptive statistic at the statistical software SPSS 27. According to the answers, Greek coaches use a dryland warm up for 5 – 10 minutes which contains dynamic exercises. The warm-up total volume in the water ranges from 400 to 800m. Specifically, technique and kick exercises are used in a volume of 100 to 150m and 50 to 100m respectively. Sets in constant intensity are used from 50 to 100m, whereas the incremented intensity sets are used in a volume from 50 to 100m. Sprint sets ranged from 12.5 to 25m, whereas, the recovery at the end of warm – up, is used in distances between 50 and 100m. Also, the coaches choose 2 starts from the block, whereas the most of them do not use flips and finishes. Concluding, the ideal duration between warm-up and swimming race, which was chosen by coaches, for the swimmers’ optimal performance is between 15 and 30 minutes, while the duration which probably could limit the beneficial properties of warm-up, is equal to or greater than 50 minutes. In conclusion, it was found that Greek coaches choose for 11 – 12 years - old swimmers, a warm-up structure similar with the older one but in a reduced volume. The results of the study can be used by researches to construct warm – up protocols in which will be examined their possible effects on childhood swimmers’ performance.